Continuous vs. discontinuous purification of isolated human islets: functional and morphological comparison - Buemi, Antoine; Mouard, Nizar I.; Darius, Tom; Devresse, Arnaud; Kanaan, Nada; Gianello, Pierre; Mourad, Michel (Frontiers in Endocrinology, 2023)
Background The COBE 2991 cell processor, commonly used for pancreatic islet isolation, is no longer distributed in Europe, leading to search for alternative purification procedures with equivalent efficacy. The aim of this study was to evaluate the efficacy of an alternative method based on the discontinuous purification of islets. Methods The conventional isolation procedure using a standard continuous islet purification with COBE 2991 of n=4 human pancreas was compared to n=8 procedures using a discontinuous purification with a “bottle” method from donors of similar characteristics. Islet equivalents, purity and dynamic glucose-stimulated insulin secretion were evaluated. Results A similar islet yield was obtained using continuous vs discontinuous purification methods (76292.5±40550.44 versus 79625±41484.46 islet equivalents, P =0.89). Islets from both groups had similar purity (78.75%±19.73% vs 55%±18.16%, P=0.08) and functionality both in terms of stimulation index (3.31±0.83 vs 5.58±3.38, P=0.22) and insulin secretion (1.26±0.83 vs 1.53±1.40 mean AUC, P=0.73). Moreover, the size of the islets was significantly larger in the discontinuous vs continuous purification group (19.2%±10.3% vs 45.4%±18.8% of islets less then 100m, P=0.0097 and 23.7%±5.3% vs 15.6%±5.8 % of 200-250m islets size, P=0.03). Conclusions Compared to the conventional purification procedure, discontinuous purification with a “bottle” method shows similar results with regards to isolation yield and islet secretory function. Furthermore, this alternative technique allows obtaining larger islets.